Accounting Education and Practice: The Singapore Experience - Tan, Teck Meng (Institutional Knowledge at Singapore Management University, 1994)
The rapid economic growth in Singapore over the last 3 decades has created a significant demand for accounting education and a need for a responsive professional accounting body to serve business and industry. A historical background of the development of accounting education and profession in Singapore is presented. The relationship between accounting education and practice is described to provide a better appreciation of the important role accounting plays in the economic growth and success of a nation. For historical reasons, corporate financial reporting practices and standard setting in Singapore are, to a large extent, patterned after the practices adopted in the UK and other Commonwealth countries.